Potential economic and clinical implications of improving access to snake antivenom in five ASEAN countries: A cost-effectiveness analysis. - Chanthawat Patikorn; Ahmad Khaldun Ismail; Syafiq Asnawi Zainal Abidin; Iekhsan Othman; Nathorn Chaiyakunapruk; Suthira Taychakhoonavudh (Public Library of Science (PLoS), 2022)
Background Despite domestic production of antivenoms in the Association of Southeast Asian Nations (ASEAN) countries, not all victims with snakebite envenomings indicated for antivenom received the appropriate or adequate effective dose of antivenom due to insufficient supply and inadequate access to antivenoms. We aimed to conduct a cost-effectiveness analysis to project the potential economic and clinical impact of improving access to antivenoms when all snakebite envenomings in ASEAN countries were hypothetically treated with geographically appropriate antivenoms. Methodology Using a decision analytic model with input parameters from published literature, local data, and expert opinion, we projected the impact of "full access" (100%) to antivenom, compared to "current access" in five most impacted ASEAN countries, including Indonesia (10%), Philippines (26%), Vietnam (37%), Lao PDR (4%), and Myanmar (64%), from a societal perspective with a lifetime time horizon. Sensitivity analyses were performed. Principal findings In base-case analyses, full access compared to current access to snake antivenom in the five countries resulted in a total of 9,362 deaths averted (-59%), 230,075 disability-adjusted life years (DALYs) averted (-59%), and cost savings of 1.3 billion USD (-53%). Incremental cost-effectiveness ratios (ICERs) of improving access to antivenom found higher outcomes but lower costs in all countries. Probabilistic sensitivity analyses of 1,000 iterations found that 98.1-100% of ICERs were cost-saving. Conclusion/significance Improving access to snake antivenom will result in cost-saving for ASEAN countries. Our findings emphasized the importance of further strengthening regional cooperation, investment, and funding to improve the situation of snakebite victims in ASEAN countries.